Ultrasound-triggered delivery of paclitaxel encapsulated in an emulsion at low acoustic pressures. Issue 8 (3rd February 2020) - Al Rifai, N.; Desgranges, S.; Le Guillou-Buffello, D.; Giron, A.; Urbach, W.; Nassereddine, M.; Charara, J.; Contino-Pépin, C.; Taulier, N.
Abstract : We investigated the in vitro ultrasound-triggered delivery of paclitaxel, a well known anti-cancerous drug, encapsulated in an emulsion and in the presence of CT26 tumor cells. Abstract : We investigated the in vitro ultrasound-triggered delivery of paclitaxel, a well known anti-cancerous drug, encapsulated in an emulsion and in the presence of CT26 tumor cells. The emulsion was made of nanodroplets, whose volume comprised 95% perfluoro-octyl bromide and 5% tributyl O -acetylcitrate, in which paclitaxel was solubilized. These nanodroplets, prepared using a high-pressure microfluidizer, were stabilized by a tailor-made and recently patented biocompatible fluorinated surfactant. The delivery investigations were performed at 37 °C using a high intensity focused ultrasound transducer at a frequency of 1.1 MHz. The ultrasonic pulse was made of 275 sinusoidal periods and the pulse repetition frequency was 200 Hz with a duty cycle of 5%. The measured viabilities of CT26 cells showed that paclitaxel delivery was achievable for peak-to-peak pressures of 0.4 and 3.5 MPa, without having to vaporize the perfluorocarbon part of the droplet or to induce inertial cavitation.